Outcomes of Microsurgical Varicocelectomy in Azoospermic Men with Varicocele: A Prospective Analysis of 50 Cases - Naqib Ullah, Sajid Shakeel, Muhammad Izhar, Zakir Khan, Navid Khan, Fahim Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Varicocele is a common correctable cause of male infertility and has been associated with impaired spermatogenesis, including azoospermia. Microsurgical varicocelectomy is considered the gold standard for its treatment, as it has low complication rate, low chances of recurrence and high success rate. Objective: This study aimed to evaluate the effectiveness of microsurgical varicocelectomy in restoring spermatogenesis in men with non-obstructive azoospermia secondary to varicocele. Methods: A total of 50 azoospermic patients with clinical varicocele underwent microsurgical subinguinal varicocelectomy at Health Net Teaching Hospital, Hayatabad, Peshawar from August 2022 to August 2023. Semen analysis was repeated postoperatively at regular intervals after six months of surgery. Results: Out of the 50 patients, 27 (54%) showed the return of sperm in ejaculate after the procedure, indicating resumed spermatogenesis. The remaining 23 (46%) did not show any sperm in follow-up semen analyses. Conclusion: Microsurgical varicocelectomy appears to be an effective treatment option for a subset of azoospermic men with varicocele, with more than half demonstrating a return of sperm production postoperatively but mostly these patient lands on ARTs. Keywords: Microsurgical Varicocelectomy, Azoospermic Men, Varicocele